2001
DOI: 10.1046/j.1523-1747.2001.14071.x
|View full text |Cite
|
Sign up to set email alerts
|

A Mannose-Binding Receptor is Expressed on Human Keratinocytes and Mediates Killing of Candida albicans

Abstract: Human keratinocytes are known to kill Candida albicans in vitro, but the mechanism of killing is not yet understood. Here, we demonstrate that spontaneous, ultraviolet-B-light-induced, alpha-melanocyte-stimulating-hormone-induced, and interleukin-8-induced Candida killing by keratinocytes can be inhibited with mannan and mannosylated bovine serum albumin (Man-BSA). A polyclonal goat serum raised against the human macrophage mannose receptor stained suprabasal keratinocytes, but no staining was observed on kera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 57 publications
1
59
0
3
Order By: Relevance
“…Remarkably, the production of TNF-␣ was significantly greater when macrophages were exposed to S. cerevisiae than to C. albicans. This observation is in concert with published data that ␤-glucan is buried within the cell wall of C. albicans and that Candida uptake by macrophages and keratinocytes can be inhibited by mannan and, to a lower extent, by glucan (37,54,90). It is also possible that S. cerevisiae may have a higher density of ␤-glucan exposed on its surface compared to that of C. albicans.…”
Section: Ebv Ebv Infection Occurring In Early Childhood Is Usually Nsupporting
confidence: 85%
See 1 more Smart Citation
“…Remarkably, the production of TNF-␣ was significantly greater when macrophages were exposed to S. cerevisiae than to C. albicans. This observation is in concert with published data that ␤-glucan is buried within the cell wall of C. albicans and that Candida uptake by macrophages and keratinocytes can be inhibited by mannan and, to a lower extent, by glucan (37,54,90). It is also possible that S. cerevisiae may have a higher density of ␤-glucan exposed on its surface compared to that of C. albicans.…”
Section: Ebv Ebv Infection Occurring In Early Childhood Is Usually Nsupporting
confidence: 85%
“…B cell knockout mice, which lack functional antibodies, are as resistant to mucosal or invasive candidiasis of endogen origin as are immunocompetent controls (97). In addition, patients with X-linked agammaglobulinemia or severe hypogammaglobulinemia do not exhibit an increased susceptibility to either mucocutaneous or invasive candidal infections (52 (19,25,54,90). Recognition and uptake of Candida yeasts involve the macrophage MR, which is a type I membrane protein with three types of domains in the extracellular region (19,54,59,93).…”
Section: Ebv Ebv Infection Occurring In Early Childhood Is Usually Nmentioning
confidence: 99%
“…Our previous study revealed that the rate constants had little effect on the output of the model and can therefore be taken from general values from the literature (Römgens et al 2016). The initial receptor concentration was estimated from the cell density (6.2 × 10 4 cells/mm 3 for the dermis, 1.3 × 10 6 cells/mm 3 for the epidermis) and the number of receptors per cell (1 × 10 5 ) for both the epidermis and dermis (Avraméas et al 1996;McLellan et al 1998;Szolnoky et al 2001;Mulholland et al 2006;Römgens et al 2016). The diffusion coefficient in both these layers was based on measurements with 40 kDa dextran (Römgens et al 2015).…”
Section: Transport and Kinetics In The Skinmentioning
confidence: 99%
“…the default values for the rate constants, initial receptor concentrations, dose per microneedle, and diffusion coefficients are presented. these were based on values reported in the literature (avraméas et al 1996;mclellan et al 1998;szolnoky et al 2001;metz et al 2003;mulholland et al 2006;ibrahim et al 2012;römgens et al 2015;Vainshtein et al 2015). these values were used in all simulations unless stated otherwise.…”
Section: Transport and Kinetics In The Skinmentioning
confidence: 99%
“…The macrophage MR, one of the best characterized C-type lectin receptor (CLR) was the first membrane receptor implicated in the recognition of Candida yeasts by human macrophages [43,44,[51][52][53]. Monocyte-derived human macrophages (MDM) ingested and killed unopsonized Candida blastoconidia but both phagocytosis and killing of unopsonized yeasts were slower than those of serum-opsonized Candida [42].…”
Section: Induction Of Th17 Differentiation By Pattern Recognition Recmentioning
confidence: 99%